The Effect of Grammar Translation Method in Description Text on Writing Ability of Class XI Vocational High School Students: Pengaruh Metode Grammar Translation Dalam Teks Deskripsi Terhadap Kemampuan Menulis Siswa Kelas XI Sekolah Menengah Kejuruan - Dinda Ayu; Dian Rahma Santoso (Academia Open, 2022)
The topic of this research is The Effect of Grammar Translation Method in Descriptive Text for Students’ Writing Skill. The objective of this research were to find how the Grammar Translation Method can improve students’ writing skill through descriptive text for eleventh grade students at SMK Yapalis Krian in the academic year of 2019/2020 and whether the grammar translation method can be used as a method in improving the students’ achievement of writing skill. The researchers was applied pre-experimental research in this study. The steps of pre-experimental research were given test and treatment. In gathering the data, the researcher used a test in the form of writing content about descriptive text. The result of this research showed that using grammar translation method was good. It was proven by the improvement mean difference of pre-test and post-test after treatment. The means of the pre-test was 60.85, and the post-test was 74.63. Therefore, it can be suggessted that grammar translation method can be used as the alternative method in teaching which especially to improve writing skill.